Evaluating an intervention to improve belt fit for adult occupants: Promoting positive beliefs. (February 2018) - Buckley, Lisa; Jones, Monica L.H.; Ebert, Sheila M.; Reed, Matthew P.; Hallman, Jason J.
Abstract: Introduction: Seat belt use provides significant public health benefit, however, most public awareness campaigns have generally focused on seat belt use rather than encouraging adults to improve seat belt fit with belt placement. This study provides an evaluation of a video-based intervention to improve adult belt fit assessing whether a video-based intervention can target beliefs and knowledge of seat belt placement and be perceived as relevant by the target audience. Method: An intervention group of 29 adults (15 women and 14 men) and a comparison group of 99 adults (41 women and 47 men) participated. Results: The intervention group had significantly more favorable beliefs around belt fit than the comparison group related to Health Belief Model constructs of higher self-efficacy, greater benefits, and fewer barriers. The intervention group was also significantly better at accurately drawing belt fit than the comparison group. The video intervention was described as relevant, interesting, and the intervention group favored the provision of a diverse sample of models in the intervention. Conclusions: Overall, the study provides insight into relevant target beliefs for an intervention focused on belt fit and suggests that a brief video-based intervention in the style of a public service announcement may be effective in promoting positive beliefs and knowledge around belt fit. Future efforts should confirm these findings with a larger sample size spanning multiple geographic and demographic areas. Practical applications: These findings can help better inform intervention initiatives to improve occupant belt fit.